Students’ performance and perceptions on continuous assessment. Redefining a chemical engineering subject in the European higher education area - Sanz-Pérez, E.S. (Education for chemical engineers, 2019)
[Display omitted] •A two-year study on a university subject with 100 students is developed.•Student feedback is essential to shape the assessment method.•Exempting midterms have a great potential to enhance learning outcome.•Correlation studies between surveyed items reveal hidden and relevant connections. Chemical Engineering taught as a subject across three Energy Engineering-based degree streams was evaluated considering two cohorts in two consecutive years after the implementation of the Bologna Process in Spain. A regular continuous assessment methodology yielded negative results during the first year. Student insight on course development, own expectations and results, and the evaluation system were then explored via a 33-item survey with participation levels between 41% and 82%. Direct answers were evaluated including rank correlations between all items. The 465 correlation coefficients obtained showed stimulating and unanticipated results. For example, it was shown that a severe grading process (external blame-assignment) was only identified as an explanation for a low mark by those students who performed most poorly in the subject and, therefore, had a poorer understanding of the materials. Besides, the feedback received from students was used to implement several changes in both the teaching practice and the assessment method during the second year, such as incorporating exam-like problems in daily classes and setting two midterm exams instead of the final one. The results registered after the second year pointed to substantial progress in student learning. Pass rates also rose from a 30% in the first academic year to 49% and 58% in the two following ones.